Characterization and Reactions of Copper (II) - Glycerol Complex - Abu Hassan, Hazimah (1998)
In solution, either aqueous or methanolic, the colour of copper(II)-glycerol complex (Cu-Gly) is deep midnight blue. Its presence was confirmed by its UV-VIS spectrum, which was a broad unsymmetrical band with a ƛmax ~625 nm. The Na₂SO₄ bisalt of the complex was successfully isolated and. characterized. The detailed characterization studies revealed interesting behaviours of the complex and its unique chemistry. The coordination of glycerol to Cu(IT) was evidenced by the absorption frequencies in the region 1500-1200 cm⁻¹ of the IR spectrum of the complex. The CHN analysis of the complex led to a proposed molecular formula of The uv-visible spectra showed absorption maxima at 381 nm and 625 nm with a shoulder at 531nm. The calculated 10Dq for the complex fell in the range of strong ligands. The structure of Cu-Gly complex ion was therefore suggested to be atetragonally distorted octahedron, with the two glycerolate ions lying in a square plane. The two water molecules were assumed to be weakly bonded at the axial positions. The study also indicated that coordination of glycerol to Cu(IT) was via its 1 ,2-hydroxyl positions. Oxidations of Cu-Gly complex were carried out in-situ, either in aqueous or methanolic media, using the following oxidants: HN03, Br2, Cr03, pyridiniumchlorochromate (PCC), H202, KMn04 and K2Cr207. Four of these gave oxidative products such as CO2, formic acid, oxalic acid and glyceric acid. These products were identified spectroscopically and confirmed by simple chemical tests, where necessary. To further understand the chemistry of Cu-Gly complex, the oxidations were also carried out on its insoluble intermediate and pure glycerol (uncomplexed). The results from this study, supported further by the identified products and the proposed mechanisms for the reactions, have shown that the coordination of Cu(II) was indeed at the l ,2-position of glycerol. The relative activities of the oxidants are parallel to the EO of their half reactions. Therefore a general trend in predicting the products (cleavage or noncleavage) can be postulated. The results of the study also show that Cu(IT) does play a major role in the reactions of Cu-Gly complex especially those involving electron transfer. The GC technique developed in this study is shown to be simple, reliable,practical and, hence, suitable for direct analyses of glycerol and its derivatives. No derivatization was required.